Efeito do treinamento com pesos, prescrito por zona de repetições máximas, na força muscular e composição corporal em idosas - da Silva, Carla Micheli; Gurjão, André Luiz Demantova; Ferreira, Leandro; Gobbi, Lilian Teresa Bucken [UNESP]; Gobbi, Sebastião [UNESP] (My University, 2006)
The aim of this study was to verify the effect of resistance training, prescribed by zone of maximum repetitions (MR), on the body composition and muscle strength in older women. Therefore, a quasi-experimental research design was used. The sample comprised 30 older women (61.1 ± 7.3 years) without health problems that could prevent them from attending the training protocol. Maximal muscle strength was measured by means of the 1-RM test while body composition was assessed by bioelectrical impedance which followed the recommendations of a 24-hour protocol regimen prior to the assessments. The resistance training protocol comprised 3 sessions per week; 2 sets of 10-to-12 RM each session and it lasted for 12 weeks. The data were analyzed by means of descriptive statistics and Student t-test for paired samples, at p<0.05 level. No statistically significant changes (p> 0.05) on body composition variables were found, except for a small decline on body mass, which, in turn, caused a small reduction on the body mass index. Increase in strength was observed (p<0.01) for both extensor and flexor knee muscles (36.5% and 34.3%, respectively) as well as for elbows (13.7% and 16.3%, respectively). The results suggested that resistance training at maximal-repetition zone allows for muscle strength increments, however, it does not affect lean body mass or percent and absolute values of body fat in older women.
Effect of resistance training, prescribed by zone of maximum repetitions, on the muscular strength and body composition in older women
Keywords: Aging; Body composition; Muscle strength; Performance; Training